An Ultrathin Flexible 2D Membrane Based on Single‐Walled Nanotube–MoS2 Hybrid Film for High‐Performance Solar Steam Generation. (22nd November 2017) - Yang, Xiangdong; Yang, Yanbing; Fu, Linna; Zou, Mingchu; Li, Zhihao; Cao, Anyuan; Yuan, Quan
Abstract: Solar steam generation is achieved by localized heating system using various floating photothermal materials. However, the steam generation efficiency is hindered by the difficulty in obtaining a photothermal material with ultrathin structure yet sufficient solar spectrum absorption capability. Herein, for the first time, an ultrathin 2D porous photothermal film based on MoS2 nanosheets and single‐walled nanotube (SWNT) films is prepared. The as‐prepared SWNT–MoS2 film exhibits an absorption of more than 82% over the whole solar spectrum range even with an ultrathin thickness of ≈120 nm. Moreover, the SWNT–MoS2 film floating on the water surface can generate a sharp temperature gradient due to the localized heat confinement effect. Meanwhile, the ultrathin and porous structure effectively facilitates the fast water vapor escaping, consequently an impressively high evaporation efficiency of 91.5% is achieved. Additionally, the superior mechanical strength of the SWNT–MoS2 film enables the film to be reused for atleast 20 solar illumination cycles and maintains stable water productivity as well as high salt rejection performance. This rational designed hybrid architecture provides a novel strategy for constructing 2D‐based nanomaterials for solar energy harvesting, chemical separation, and related technologies. Abstract : To address the difficulties in obtaining photothermal materials with ultrathin structure yet sufficient solar spectrum absorption capability, an ultrathin and self‐floating SWNT–MoS2 hybrid film is designed. As an interfacial heating membrane, this SWNT–MoS2 film shows enhanced steam generation efficiency and superior recycle stability due to the ultrathin and porous structure as well as high mechanical strength.